The impact of trunk impairment on performance-determining activities in wheelchair rugby - Altmann, V. C.; Groen, B. E.; Hart, A. L.; Vanlandewijck, Y. C.; van Limbeek, J.; Keijsers, N. L. W. (Scandinavian Journal of Medicine & Science in Sports, 2017)
In Paralympic sport, classification of impairment is needed to prevent a one-sided and predictable outcome of competition, in which the least impaired athlete has the best chance to win. To develop evidence-based classification in wheelchair rugby, the impact of trunk impairment, measured by the Trunk Impairment Classification (TIC), on performance-determining activities was assessed. Arm impairment was analyzed as a covariant. Fifty-five athletes, 21 with TIC score 0, 13 with TIC score 0.5, 11 with TIC score 1.0, and 10 with TIC score 1.5 performed standardized sport-specific activities. A multiple step forward regression analysis was performed for all activities to assess the relative impact of trunk and arm impairment on performance. Trunk impairment was the most important factor for tilting the chair and acceleration in the first 2 m. The explained variance of the performance by trunk and arm impairment ranged from 23% for acceleration in the first meter, to 37% for sprint momentum, the tilt test left, and the time to cover 3 and 4 m. This study shows that athletes with limited trunk impairment are more proficient in wheelchair rugby than athletes with severe trunk impairment.